Aconiti Lateralis Radix Praeparata as Potential Anticancer Herb: Bioactive Compounds and Molecular Mechanisms - Zhang, Wen; Lu, Chaoying; Cai, Shuhui; Feng, Yaru; Shan, Jinjun; Di, Liuqing (Frontiers in Pharmacology, 2022)
Aconiti Lateralis Radix Praeparata (Fuzi in Chinese) is a traditional herbal medicine widely used in China and other Asian countries. In clinical practice, it is often used to treat heart failure, rheumatoid arthritis, and different kinds of pains. Fuzi extract and its active ingredients exert considerable anticancer, anti-inflammatory, and analgesic effects. The main chemical substances of Fuzi include alkaloids, polysaccharides, flavonoids, fatty acids, and sterols. Among of them, alkaloids and polysaccharides are responsible for the anticancer efficacy. Most bioactive alkaloids in Fuzi possess C19 diterpenoid mother nucleus and these natural products show great potential for cancer therapy. Moreover, polysaccharides exert extraordinary tumor-suppressive functions. This review comprehensively summarized the active ingredients, antineoplastic effects, and molecular mechanisms of Fuzi by searching PubMed, Web of Science, ScienceDirect, and CNKI. The anticancer effects are largely attributed to inducing apoptosis and autophagy, inhibiting proliferation, migration and invasion, regulating body immunity, affecting energy metabolism, as well as reversing multidrug resistance. Meanwhile, several signaling pathways and biological processes are mainly involved, such as NF-κB, EMT, HIF-1, p38 MAPK, PI3K/AKT/mTOR, and TCA cycle. Collectively, alkaloids and polysaccharides in Fuzi might serve as attractive therapeutic candidates for the development of anticancer drugs. This review would lay a foundation and provide a basis for further basic research and clinical application of Fuzi.